Climate Change Impacts on Energy Generation from Renewable Energies in the Island of Crete, Greece - Vourdoubas, John (Environmental Management and Sustainable Development, 2022)
Renewable energies are expected to have a central role in the future zero carbon economy. However, their energy potential is affected by climate change. The current work investigates the future impacts of climate change on the energy potential of several renewable energies including solar energy, wind energy, biomass and hydro energy in the island of Crete, Greece. Previous research worldwide has indicated that climate change is going to affect positively or negatively the potential of various renewable energies while the impacts are different in various geographical areas. The goal of the current study is the evaluation of the impacts of climate change on the energy potential of solar energy, wind energy, hydro energy and biomass in the island of Crete. Our results indicated that climate change during 21th century is expected to increase the solar energy potential in Crete by around 4% while the wind energy potential is going to decrease by 6-12%. A slight decrease in annual precipitation in the island is foreseen while the agriculture and forest-related solid biomass potential is expected to decrease due to more frequent forest fires, more droughts and land desertification. Climate change is not going to affect significantly the potential of the rich solar and wind energy resources in Crete. The findings of the present study could be useful in sizing the new renewable energy systems in Crete which are required to generate the “carbon-free energy” in the emerging “zero-carbon economy” by 2050.